KOLABORASI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA PEKANBARU DENGAN PERANGKAT KECAMATAN BINA WIDYA DAN KELURAHAN TOBEK GODANG DALAM PERBAIKAN JALAN DELIMA TAHUN 2022-2023 - Inzaghi, Fajri Dwi; ,, Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study, entitled "Collaboration between the Public Works and Spatial Planning Agency of Pekanbaru City, the Binawidya District Apparatus and the Tobek Godang Village in the Repair of Jalan Delima in 2022–2023," aims to analyze the forms, mechanisms, and effectiveness of collaboration between government agencies in improving road infrastructure in urban areas. The background of this research is based on the importance of addressing the damage to Jalan Delima, one of the access roads that supports public mobility and economic activity in Pekanbaru City. The recurring problem of damaged roads demands more coordinated collaboration between the Public Works and Public Housing Agency as the technical implementer and regional apparatus as the field data provider and communication bridge with the community. The research method used was descriptive qualitative, with data collection techniques through interviews, field observations, and documentation. The results indicate that the collaboration between the Public Works and Public Housing Agency, the Binawidya District, and the Tobek Godang Village can be categorized as effective, although it still faces a number of technical and administrative challenges. This collaboration is carried out through a structured coordination process, a fairly intensive exchange of information, and a clear division of tasks based on the authority of each agency. The active role of sub-district and village officials in providing damage data, facilitating communication with the community, and conducting field monitoring has accelerated the repair process. Keywords: Inter-agency Collaboration, Regional Government, Road Infrastructure